Problematika Lingkungan Hidup dalam Lirik Lagu Rock “Lupa Aturan”: Studi Ekologi Sastra - Rizal Maulana Ishaq; Sahrul Romadhon (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Literary Ecology This research aims to analyze environmental problems in the lyrics of the rock song “Forgot Rules” using literary ecology studies. This research was conducted using a descriptive qualitative approach. The data source in this research is the lyrics of the rock song “Forgot Rules” Soul Patriot on the ADEWE MUSIC YouTube account channel. The data in this research are words and sentences in the lyrics of the rock song “Forgot Rules”. The data analysis technique used consists of three stages, namely listening to the rock song “Forgot Rules” on the ADEWE MUSIC YouTube channel, identifying (determining data), describing (depiction of data accompanied by appropriate references). The results of this research related to environmental problems in the lyrics of the rock song “Forgotten Rules” are (1) Statements related to environmental conditions, (2) Satire related to environmental conditions, (3) criticism related to environmental conditions and (4) reflections related to environmental conditions. Environment.